ALIH KODE DALAM ACARA TV TALK SHOW INDONESIA HITAM PUTIH - KARUNIA, RURI (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2018)
ABSTRACT The research is entitled “Code Switching on Indonesian Tv Talk Show  Hitam Putih. The objective of this research is to identify, classify, and analyze the types and factor of code switching on this program. The data were elicited from five conversations between host and the guest star on Hitam Putih which were taken from youtube.  In analyzing the data, the writer uses the theory of Poplack (1980) to analyze the types of code switching and Fishman’s theory (1976) to find out the factor of code switching. Descriptive method is used in this research The result shows that the types of code switching found on this program are;Tag switching, Intrasentential switching,Intersentential switching and the factors that caused this code switching are; speaker, listener or opponent, the presence of a third person, change of subject. This research is expected to give a contribution in the study of sociolinguistics especially on the subject of code switching for the development of sociolinguistics at the Faculty of Humanities, Sam Ratulangi University and to help the readers or students to learn sociolinguistics,  especially to add their knowledge about code switching.  Keywords : Code Switching , Talk Show, Hitam Putih, Descriptive Analysis